"This Great Crisis in the Republick of Letters" - The Introduction in 1712 of Stamp Duties on Newspapers and Pamphlets - Sadler, Pauline; Oats, L. (Sweet and Maxwell, 2002)
Stamp duty is currently undergoing a transformation which includes a reformulation of its scope.Early in its 300-year life, however, stamp duty extended to a much more diverse range of transactions and also to some goods, including newspapers and pamphlets.This paper examines the imposition of stamp duty on the press in 1712, during the reign of Queen Anne. The stamp duty on newspapers and pamphlets was intended both as a revenue raiser, and as a means of silencing the press by putting them out of business. The Government avoided direct censorship, but creatively used taxation to impose indirect censorship.The stamp duty reflected the recognition by the Government of the growing influence of the media on the political and social life of the period and it was, in effect as well as intention, a method of social control. As if often the case with tax measures adopted for ulterior motives the legislation proved to be inadequate with ample opportunity for avoidance and evasion.